2015
DOI: 10.1080/08927014.2015.1011067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mixed biofilm (Staphylococcus aureusandPseudomonas aeruginosa)by laser ablation electrospray ionization mass spectrometry

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are ubiquitous pathogens often found together in polymicrobial, biofilm-associated infections. This study is the first to use laser ablation electrospray ionization mass spectrometry (LAESI-MS) to rapidly study bacteria within a mixed biofilm. Fast, direct, non-invasive LAESI-MS analysis of biofilm could significantly accelerate biofilm studies and provide previously unavailable information on both biofilm composition and the effects of antibiofilm treatment. LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…P. aeruginosa Green-fluorescent protein (GFP) + and S. aureus Red-fluorescent protein (RFP) + were used for these studies. 19 The cells were incubated for 24 h in tryptic soy broth (TSB) medium in the presence of DRGN-1. The next day, the wells were rinsed and the development of a biofilm was compared with a control well (without DRGN-1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. aeruginosa Green-fluorescent protein (GFP) + and S. aureus Red-fluorescent protein (RFP) + were used for these studies. 19 The cells were incubated for 24 h in tryptic soy broth (TSB) medium in the presence of DRGN-1. The next day, the wells were rinsed and the development of a biofilm was compared with a control well (without DRGN-1).…”
Section: Resultsmentioning
confidence: 99%
“…Biofilms of both P. aeruginosa and S. aureus were significantly reduced by DRGN-1. In mixed-culture biofilms grown for 24 h without treatment, P. aeruginosa significantly outgrows S. aureus , 19 thus the appropriate starting ratio was established as a 99:1 ratio S. aureus to P. aeruginosa . Treatment with DRGN-1 had a significant inhibitory effect on the mixed bacterial cultures in contrast with untreated control.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many advanced versions of the FISH technique have been implemented for different purposes, most commonly; catalyzed reporter deposition-FISH (CARD-FISH) for fluorescent signal enhancement (Lupini et al, 2011), peptide nucleic acid-FISH (PNA-FISH) for better penetration and faster hybridization (Werthén et al, 2010) and CLASI-FISH for expanding the number of distinguishable taxa in complex communities (Valm et al, 2012). In addition, an innovative technique, laser ablation electrospray ionization mass spectrometry (LAESI-MS), has been used for studying the spatial distribution of mixed species biofilms and is showing potential advantages contrasted to CLSM experiments (Dean et al, 2015), as LAESI-MS allows for rapid analysis of unfixed and wet biofilms.…”
Section: Methods To Examine and Link The Spatial Organization To Biolmentioning
confidence: 99%
“…Dean et al [30] analyzed mixed biofilm of S. aureus and P. aeruginosa by laser ablation electrospray ionization mass spectrometry, and found that S. aureus and P. aeruginosa within the mixed biofilm showed significant colocalization of the cells, rather than self-segregation. Thus, the growth rate of coculture biofilms could be in between the growth rate of monospecies biofilms (that is, greater than P. aeruginosa and less than S. aureus ), according to the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%